PENGARUH E-COMMERCE TERHADAP PERTUMBUHAN EKONOMI DI LIMA NEGARA ASEAN - Paramitha, Diva Trevina Salsabilla; Eva Ervani (Cahaya Ilmu Bangsa, 2024)
Abstrak Digitalization has completely changed the business landscape, with e-commerce being one of the most affected sectors. The surge in internet users has encouraged people to use e-commerce purchasing access. The aim of this research is to determine the influence of e-commerce on economic growth in Indonesia, Malaysia, Singapore, Thailand and the Philippines using annual panel data from 2017 to 2022. After reviewing the data, researchers used the Fixed Effect Model estimation technique. The research results show that e-commerce has a significant impact in increasing economic growth in five ASEAN countries. Apart from that, control variables such as population and labor force participation also show a significant influence on economic growth. Therefore, policy makers are advised to design effective and appropriate digitalization policies, especially e-commerce, to increase sustainable economic growth in the five ASEAN countries. Kata kunci: E-commerce, Economic Growth, Panel Data